Electric Field Mitigation for String Insulators using Corona Ring and Zinc-Oxide (ZnO) - Abdul Ghafar, Umarull Hashimi; Kamarudin, Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2023)
The simulation results of the electric field distribution along cap and pin insulators on various mitigation techniques under dry-clean and polluted conditions are presented in this paper. The behavior of the electric field along the insulator string is examined using the finite element method (FEM). For this study, the modeling and execution of the electric field analysis are done using COMSOL Multiphysics version 6.0. In this study, the effectiveness of corona rings and Zinc-Oxide (ZnO) micro-varistors as tools for reducing the increase in electric field intensity was investigated. To investigate the impact of pollution and mitigation strategies on the distribution of the electric field on the surface of the insulator, reference data from dry-clean conditions were used as the benchmark. It was found that the application of combined methods of corona rings and ZnO is the best scheme for stress control as it reduced the electric field intensity up to almost 3% for both dry-clean and polluted conditions.